Effects of temperature on vapor liquid equilibrium of MTBE-methanol mixtures - Mohamad Azamudin, Ishak (2010)
In separation process of binary mixture the vapor liquid equilibrium diagram is integral to design the separation apparatus. This research objective is to construct the vapor liquid equilibrium diagram for MTBE-Methanol binary mixture system at various temperatures and at constant pressure. Other objective is also to find the Azeotropic point which the MTBE-Methanol binary mixture formed at certain point that posed problems in separation processes. The separation process encountered problems during the Azeotropic point which vapor and liquid fraction is equal. The equipment used is Vapor Liquid Equilibrium Unit Equipment in the Unit Operation Laboratory. Initially the steps taken are to find the calibration curve for MTBE-Methanol mixture. The experiment started with MTBE volume set at constant and gradually increase the Methanol volume. The mixture in the equipment will be heated at four different temperatures which will give enough data to construct the diagram. Record the RI index and the temperature. The experiment was conducted at four different temperatures. The result, MTBE fraction of x vapor fraction and y liquid fraction formed Azeotropic point at 0.6~0.7 x =y.